Compressive Behavior of Corroded RC Columns Strengthened With Ultra-High Performance Jacket - Chen, Jun; Wang, Zongshan; Xu, Anqi; Zhou, Jianting (Frontiers in Materials, 2022)
This paper performed compressive tests on corroded reinforced concrete (RC) columns with externally confined ultra-high performance concrete (UHPC) jacket. The studied parameters in this testing program was the corrosion ratio of specimens. The influences of this parameter on the compressive behavior of concrete columns confined by UHPC jacket was reported and discussed. The test results revealed that when the rust rate was less than 20%, axial cracking was the typical failure mode of unreinforced specimens, and the cracks in the rusted area gradually increased with the increase of the rust rate. When the corrosion rate reached 30%, the concrete of the protective layer fell off significantly, and the longitudinal reinforcement also yielded. The ultimate load and peak displacement of the specimens reinforced with UHPC were significantly improved, and the improvement rates of the two were more than 80% and 30%, respectively. The failure mode of the specimen with a corrosion rate of 30% also changed to longitudinal cracking of the UHPC layer. An analytical model was proposed to predict the ultimate load of RC columns with externally strengthening UHPC jacket. The validations of the predictions against the reported test results confirmed the accuracy of the analytical model.